Penerapan Model Pembelajaran Berbasis Proyek untuk Meningkatkan Keterampilan Proses Sains Siswa pada Konsep Pencemaran Lingkungan di SMP - Cut Zaitun Umara; Cut Nurmaliah; Khairil Khairil (Biotik, 2016)
The purpose of this study is to improve science processing skills of students of SMPN 8 Banda Aceh in the concept of pollution and environmental degradation by using project-based learning. An experimental method with pretest-posttest control group design was used in this study. The population was all students of class VII SMPN 8 Banda Aceh which consisted of 5 classes with total number was 130 students. The samples were selected by using simple random sampling technique. There were 44 students from VII-1 acted as control group and class VII-2 acted as experimental group. The data were gathered by using pre-test and post-test. The research instruments used were essay questions to measure science processing skills, student’s work sheet, and work assessment’s rubrics based on science processing skills. The data then analyzed by calculating the post-test and pre-test gain and t-test to compare between the experimental class and control class. They were analyzed by using independent sample t-test. The results showed that there were improvement in the average of science processing skills of students in project-based learning’s class for about 51.86 (high) and conventional learning class for about 38.02 (medium). T-test results obtained as follows: tvalue was 2.680 and ttable was 2.021, so tvalue>ttable. The conclusion was the implementation of project-based learning in the concept of pollution and environmental degradation improved the science processing skills of student of SMPN 8 Banda Aceh.